(untitled) (Journal of Philosophy Culture and Political Science, 2026)
The digitalization of education in Kazakhstan is analyzed as a process of cultural paradigm shift: the transition from classical epistemology to a network model of knowledge. This transformation is driven by the growing use of EdTech platforms and the integration of artificial intelligence into the educational and research infrastructure of higher education institutions. The research was carried out in line with social philosophy, philosophy of education and digital anthropology in the context of modernization of higher education in the Republic of Kazakhstan. The purpose of the research is to philosophically comprehend the digital transformation of higher and postgraduate education in the Republic of Kazakhstan as a paradigmatic shift from humanistic epistemology to a network model of knowledge in a super-complex environment. The theoretical basis of the research synthesizes the concept of «supercomplexity» by R. Barnett and the ontology of the «infosphere» by L. Floridi. The methodology of this work is interdisciplinary in nature, the research strategy is built on three interrelated levels, integrating philosophical and conceptual analysis, empirical verification and systemic synthesis. The result was the author’s model «Barnett’s Infosphere» (tetrad: information agents, reflexive nodes, flows, ethical shell). Epistemological risks are identified: metric reduction (KPI); algorithmic neocolonialism; the crisis of subjectivity of «inforg». The scientific value and practical significance of the Barnett Infosphere model lies in the possibility of its use by regulators (the Ministry of Science and Higher Education of the Republic of Kazakhstan) to form strategies for «critical digitalization» that minimize epistemic threats to AI integration and preserve the anthropological value of educational and research search. Keywords: Barnett’s infosphere, cultural paradigm, supercomplexity, epistemic friction, digitalization.